The recruitment and effect to the project performance - Wan Mohamad Aim Emirul Faiez, Wan Salleh (2015)
This research was carried out to study the recruitment and effect to the project performance. Recruitment is the process of generating a pool of capable people to apply for employment or the process of attracting, evaluating, and hiring employees in an organization. There are four elements of recruitment that investigate in this study, there is a screening process, test sessions, interview and induction program. While, an element that used to measure performance is the schedule and budget and quality deliverables. The quantitative data collection method and simple random sampling technique had been used. The target population was human resource manager and financial officer that has a background in construction. The number of samples in this research is taken according to Krejcie & Morgan table. The number of population is 86. Thus, the number of samples of this research will be 71. The questionnaire based survey was used and 80 sets of questionnaires were distributed to respondents. Questionnaires analyzed by SPSS.Correlation test will be used to investigate the relationship between two variable and mean score analysis to know which element of recruitment should emphasized.